Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Kembang Jawa Permai Kediri - Arthaviyana Fresti Romadania; Ustadus Sholihin; Zulfia Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2023)
The development of human resources in a company really requires good performance from employees, therefore employees are the benchmark for whether or not the company's goals have been achieved. This research aims to analyze the influence of workload and work environment on employee performance at PT. Javanese Flowers Permai Kediri. The analytical method in this research is quantitative descriptive with multiple linear regression analysis tools. The results of this research show that the workload variable partially influences employee performance as evidenced by the results of the t test with a significance value of 0.001<0.05. Work environment variables partially influence employee performance as evidenced by the results of the t test with a significance value of 0.004<0.05. The workload and work environment variables simultaneously influence employee performance as proven by the results of the f test with a significance value of 0.000<0.05.